Status Keharaman Produk yang Mendukung Agresi Israel terhadap Palestina (Studi Analisis Fatwa MUI No. 83 Tahun 2023): Product Legitimacy Supporting Israeli Aggression Against Palestine (Analysis Study of MUI Fatwa No. 83 of 2023) - Fachrudin, Fachrudin; Khaerul Aqbar; Rachmat Bin Badani Tempo (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to understand and analyze the Indonesian Ulema Council (Majelis Ulama Indonesia, MUI) Fatwa number 83 of 2023 regarding the prohibition status of products that support Israel's aggression against Palestine. The issue addressed in this study is: how does the analysis of MUI Fatwa no. 83 of 2023 relate to the prohibition status of products that support Israel's aggression against Palestine. This study is a literature review (library research) utilizing a qualitative descriptive method and employing normative juridical and conceptual approaches. The research findings are as follows: MUI Fatwa number 83 of 2023 establishes that all forms of support for the Palestinian struggle are mandatory, while actions, whether direct or indirect, that support Israel's aggression are deemed forbidden. The status of prohibition on products supporting Israel's aggression against Palestine in Islamic jurisprudence is known as